New finds of Cryphonectria parasitica and the first record of chestnut blight on red oak Quercus rubra L. in the Czech Republic - P. Haltofová; L. Jankovský; D. Palovčíková (Journal of Forest Science, 2005)
The causal agent of the chestnut blight, the fungus Cryphonectria parasitica (Murrill) M. E. Barr (syn. Endothia parasitica (Murrill) P. J. Anderson et H. W. Anderson), was found out at new localities in the Czech Republic. The chestnut blight was observed for the first time in the Czech Republic in 2002. Two new localities were discovered in southern Moravia in May and June 2004. The disease was identified both on the sweet chestnut (Castanea sativa Mill.) and on the red oak (Quercus rubraL.). Infected trees were treated according to the order of the State Phytosanitary Administration of the Czech Republic.